2012
DOI: 10.4161/cc.22215
|View full text |Cite
|
Sign up to set email alerts
|

DNA2 and EXO1 in replication-coupled, homology-directed repair and in the interplay between HDR and the FA/BRCA network

Abstract: During DNA replication, stalled replication forks and DSBs arise when the replication fork encounters ICLs (interstrand crosslinks), covalent protein/DNA intermediates or other discontinuities in the template. Recently, homologous recombination proteins have been shown to function in replication-coupled repair of ICLs in conjunction with the Fanconi anemia (FA) regulatory factors FANCD2-FANCI, and, conversely, the FA gene products have been shown to play roles in stalled replication fork rescue even in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 58 publications
12
95
0
Order By: Relevance
“…A similar phenotype has been observed in DNA2-depleted cells (18). Although the previous studies did not address the relationship between WRN and DNA2, they demonstrated that these enzymes act synergistically with EXO1 to promote DNA end resection in human cells (18,52). A role for WRN as a critical DNA end resection factor is also consistent with the cellular phenotype of Werner syndrome, a severe premature aging disorder caused by inherited mutations in the WRN gene (53).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…A similar phenotype has been observed in DNA2-depleted cells (18). Although the previous studies did not address the relationship between WRN and DNA2, they demonstrated that these enzymes act synergistically with EXO1 to promote DNA end resection in human cells (18,52). A role for WRN as a critical DNA end resection factor is also consistent with the cellular phenotype of Werner syndrome, a severe premature aging disorder caused by inherited mutations in the WRN gene (53).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, it has been demonstrated that WRN depletion leads to a marked reduction in the frequency of RPA and BrdU/ssDNA foci formed in response to ionizing radiation, indicative of a resection defect (52). A similar phenotype has been observed in DNA2-depleted cells (18). Although the previous studies did not address the relationship between WRN and DNA2, they demonstrated that these enzymes act synergistically with EXO1 to promote DNA end resection in human cells (18,52).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…50,55 Simultaneous depletion of BLM and EXO1 in U2OS cells treated with CPT significantly impairs RPA phosphorylation and focal accumulation, as well as the consequent ATR-mediated signaling. 50 Human DNA2 facilitates repair of replication-associated DSBs by promoting ssDNA formation at stalled replication forks, 56,57 acting redundantly with hEXO1. 48,57 In vitro data confirm that end resection occurs through two pathways, suggesting that the relationship between BLM-DNA2 and hEXO1 is not simply complementary.…”
Section: Rscmentioning
confidence: 99%
“…DNA2 and EXO1 have been shown to be important in end resection during DSB repair [195,197]. Interestingly, although DNA2 and EXO1, working in concert, are necessary for DNA end resection, their depletion results in a defect in SSA and an increase in HR [345]. Thus, it appears the role of these nucleases during end resection alters the balance between which repair pathway is utilized.…”
Section: Chapter 4: Discussionmentioning
confidence: 99%